Mathematical modelling of wave impact on landward-inclined and seaward-inclined seawalls - Mohd Shahridwan, Ramli (2019)
Shoreline and ocean structures are subjected to breaking wave loads which may reach 690kNm−2. To reduce these loading, we might slope the exposed surface seaward or landward. However, it is unclear that sloped walls can reduce the wave impact and recent models tests indicated that sloped walls might be exposed to higher loads than vertical walls. Motivated by these findings, we perform a theoretical study of wave impacts on sloped seawalls. The mathematical models of wave impacts on landward-inclined and seaward-inclined seawalls are considered by using an extension of Cooker’s model for vertical seawalls. The pressure impulse theory proposed by Cooker is applied into these two problems which simplify the highly time-dependent and very nonlinear problem by considering the time integral of the pressure over the duration of the impact pressure-impulse. The solution to this problem is found by solving Laplace’s Equation for specific boundary condition. The perturbation theory is applied into these models and the problems are solved by using MATLAB. The correlation between the pressure impulse and the inclination angle of the wall is investigated. The results are found to be in good agreement with the experimental study. It was found that the lowest pressure impulse occurs when the small inclination happens near to the vertical wall. Study also shows that pressure impulse increases as impact region increases. Breaking wave pressures increase to 17% for landward inclined wall and to 20% for seaward inclined wall compared to vertical wall at 10° incline with impact region of 0.5. Design recommendations were found to be conservative.